Development of a Two-Tier Diagnostic Test for The Analysis of Momentum and Impulse Learning Difficulties in Students - Handjoko Permana; Supriyati, Yetty; Muliyati, Dewi; Sekartaji, Ananda Ayu Dewi; Morales, Marie Paz E.; Ambarwulan, Diah (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2023)
This study aimed to develop a formation test that also serves as a diagnostic test. The purpose of this product is to determine students’ learning difficulty levels. We used a two-step multiple-choice assessment tool to develop this diagnostic test. Because two-step multiple-choice tests help teachers identify learning difficulties that arise in students. The research method used is research and development. This test was developed using the Moodle platform and takes the form of a closed multiple-choice test consisting of 20 questions. Media and materials experts validate diagnostic tests. Based on validation, this developed product can be used as a physics learning assessment tool to measure student learning outcomes and learning difficulties. The aspects of media learning expert is usability, navigation, visuals, product, effectiveness, and content. While, the aspects of material expert are compliance with curriculum, construction, and language. We tested high school students and found that 2 of the 20 questions about the concepts of momentum and impulse were mastered and the remaining 18 were at the level of instrumental understanding and misunderstanding. Therefore, teachers should look for strategies to expand students' conceptual knowledge of dynamics and momentum. Thus, the mastery of the student's concept is whole and thorough.